EBV‐directed viral‐specific T‐lymphocyte therapy for the treatment of EBV‐driven lymphoma in two patients with primary immunodeficiency and DNA repair defects. Issue 3 (18th December 2019) - Rubinstein, Jeremy D.; Burns, Karen; Absalon, Michael; Lutzko, Carolyn; Leemhuis, Tom; Chandra, Sharat; Hanley, Patrick J.; Keller, Michael D.; Davies, Stella M.; Nelson, Adam; Grimley, Michael
Abstract: Children with ataxia telangiectasia (AT), a primary immunodeficiency caused by mutations in ATM, which is critical for repairing DNA defects, are at risk for the development of hematologic malignancy, frequently driven by infection with Epstein‐Barr virus (EBV). Conventional chemotherapy is poorly tolerated by patients with AT, with excessive toxicity even when doses are reduced. Here, we report on two patients with AT and EBV‐positive neoplasms who were treated with EBV‐targeted viral‐specific T cells (VST). One patient had a prolonged complete response to VSTs while the other had a partial response. Therapy was well tolerated without infusion toxicity or graft‐versus‐host disease.